Dermatologic toxicities of chemotherapy: an educational intervention for skin of color women with breast cancer - Maham Ahmad, BA; Sabrina Saeed, BA; Brianna Olamiju, MD; Andrea Silber, MD; Jonathan Leventhal, MD (Wolters Kluwer, 2023)
Background:. Minority patients are more likely to require dose adjustments for chemotherapy, with cultural barriers and access to medical care cited as contributory factors. Objective:. We sought to pilot an educational intervention, in the form of a pamphlet, to evaluate the effectiveness of this tool in teaching skin of color (SoC) patients about potential dermatologic toxicities of chemotherapy that are relevant to their skin type. Methods:. At a chemotherapy infusion center, SoC patients (n = 26) who were receiving chemotherapy for breast cancer voluntarily consented to read an educational pamphlet and complete a series of survey questions before and after this educational intervention. Results:. Most participants identified as female (96%), African American/Black (81%), and non-Hispanic (85%); all respondents had obtained at least a high school degree. Survey responses revealed a significant increase in knowledge about the potential dermatologic effects of cancer treatment after this intervention. Notably, 100% of participants either agreed or strongly agreed that they would like to see other doctors use this educational tool as a form of patient education, that they would recommend this pamphlet to other patients who are starting cancer treatment, and that the pamphlet was easy to understand. Limitations:. Limitations of this study include small sample size and single-institution recruitment, which may limit generalizability. Furthermore, this study only included patients who are proficient in English. Conclusion:. This study pilots an effective educational tool that addresses dermatologic toxicities of chemotherapy that are relevant to SoC patients. Further multi-institutional studies with larger sample sizes and translation to other languages can overcome the limitations of this pilot study.